Formulasi Dan Uji Aktivitas Anti Bakteri Masker Gel Peel-Off Ekstrak Daun Pacar Air (Impatiens balsamina linn.) Dengan Kombinasi Basis PVA dan HPMC - Saputra, Sony Andika; Lailiyah, Munifatul; Erivina, Adella (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
Peel-off gel mask is one of the practical masks, because after dry the mask can be directly removed without rinsing. In this research, a peel-off gel mask formulation from a pacar air leaf extract (Impatiens balsamina Linn.) Has antibacterial activity against Staphylococus Aureus bacteria. The peel-off gel mask is prepared in 3 formulas by varying the PVA and HPMC concentrations of F1 (1: 2,6), F2 (1: 3), F3 (1: 3,5). Evaluation of gel quality used is organoleptic test, viscosity, adhesion, drying time, dispersion, pH. Testing of antibacterial activity was done by using the diffusion method of wells. The positive control used was clindamycin phosphate 1.2%, the negative control used was the base of the peel-off gel mask. Results of physical evaluation and antibacterial activity test were analyzed using SPSS software with trust level of 0.05. Based on the results obtained F3 is the optimum formula, because F3 has a corresponding pH of 5.2 ± 0.10, the corresponding depth of 6.85 ± 0.13, the fastest drying time of 21.68 ± 0.33 and the anti-activity the best bacteria. Based on testing of antibacterial activity of F1, F2 and F3 have antibacterial activity against Staphylococus Aureus bacteria.